Asy syudzudz Al Jinsy 'inda Madzahib Al Arba'ah wal Al Qounun Al 'Uqubat - Maulana, Syafruddin; , Dr. Muh. Muinudinillah Basri, MA; , Dr. Muthoifin, M.Ag (2014)
The development of social interactions variety and the flow of information that brings positive and negative value, impact on social life and human behavior. Among them there is a wise attitude by always making religion as a guide and lifestyle, but some people lost his life orientation. Even penetrated the lifestyle associated with sexual behavior. Sexual behavior is one of the serious issues detil discussed in Islam. This is because the impact is very wide in various aspects of life. Islam considers that the biological need is the sunnah of life that every Muslim must live, in order to achieve the balance between the human side as a servant of Allah Ta'ala and as a keeper of the stability of social life of society.Sex disorientation is a threatening balance. That will affect the survival of human life in general or personal perpetrators. Among the disorientation is lesbi, gay, have sex with animals or known as zoofilia, also the trangender which is one of the identity of lesbian and gay. This study aims to examine whether the laws and sanctions of these sexual disorientations, presented comparatively between Islamic law and Indonesian criminal law.The results of this study concluded about the prohibition of lesbian, gay, zoophilia and trangender in Islamic law. While about the punishment, there are some differences between the 4 Imams. Some give death penalty. Some others conclude about the enactment of ta'zir where the judge is given a policy in determining the type of punishment.While in Indonesian, this is contained in the chapter asusila. Which concludes that lesbian, gay, zoofilia is something that gets a criminal penalty and is binding only on an adult perpetrator with as a victim is an immature child. As for if the perpetrator and the victim is mature, then not touched with criminal trap. And the trangender has not regulated it specifically.